P015 BASHH MSM SIG Clinic Survey; Testing and vaccination. (30th June 2016) - Clutterbuck, Dan
Abstract : Background/introduction/Aim(s)/objectives: Our aim was to investigate practice across the UK in aspects of the clinical care of MSM who are HIV negative or of unknown status where evidence is absent, or guidance varies. Methods: An online questionnaire was drafted by the MSM SIG, tested by BASHH CGC members, revised and distributed to BASHH, FSRH members and CSP audit sites for one month to 31 st October 2015. Results: There were 149 complete responses. Only 40% of respondents had a written protocol or policy on recall for HIV/STI testing of which 23% had an automated system to recall patients for testing. 50% routinely test for HIV at syphilis follow up. 90% of respondents report using both NAAT and culture for GC in contacts of gonorrhoea and 20% use both in asymptomatic men. 33% test anatomical sites according to sexual contact history. Self-taken throat (rectal) swabs for GC/Ct NAAT were used never by 26% (3%) and routinely in 18% (22.5%). 100%routinely test MSM for Hepatitis B exposure and over 50% forHepatitis C. 78% routinely check HepB sAb levels following vaccination. 79% routinely recall men for Hepatitis B vaccination. Discussion/conclusion: There is evidence of variation in clinical practice between clinics in the UK, not all of which can be explained by variations in local epidemiology and some of which has significant cost implications. Results have generated debate in the MSM SIG on the rationale for local policies.